Assessing the Suitability of Clinical Programs for Implementation - Bartholomew , Tom (International Journal of Psychosocial Rehabilitation, 2016)
Mental health organizations looking to implement new clinical programs are faced with an ever-increasing number of options to choose from. Determining which program(s) to implement is often based on a fondness for “pet programs” and factors such as the availability of vender packages that may have little bearing on the appropriateness of a given program. A nine-dimension rubric is proposed as a way of measuring a program’s suitability for implementation. This rubric involves an assessment of a program’s: objective(s), efficacy, gen- eralizability, cost benefit profile, opportunity cost(s), fidelity measurement, outcome assessment, feasibility, and three factors related to implementation. These dimensions of suitability are presented as score-able criter- ia to offer organizations a means to compare and contrast various clinical programs. Programs are scored, ideally first by venders or program advocates, then individually by those charged with making a decision about implementation. Lastly, consensus is sought on scores across the nine-dimension rubric using the measurable anchors. Limitations of this approach are discussed. Future work in this area is recommended. The authors have no financial disclosures or conflicts to report.